METHODS OF TEACHING AVIATION TERMS TO THE STUDENTS USING INTERACTIVE ACTIVITIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article focuses on an assumption of using interactive methods, which can be applied for ESP students. Therefore , the researcher discusses outcomes of interactive methods, conducted lessons, and offers not only suggestions for organizing effective classes, but also presents a variety of activities for success of teaching special terms to ESP students.